2018
DOI: 10.12669/pjms.341.13485
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of collaborative problem solving skills in Undergraduate Medical Students at Ziauddin College of Medicine, Karachi

Abstract: Objective:Collaborative Problem Solving Empirical Progressions from the Assessment and Teaching of 21st Century Skills (ATC21S) framework were used to determine the level of collaborative problem solving skills (CPS) in first, second and third year MBBS students at Ziauddin College of Medicine during Problem-Based Learning (PBL) sessions. Variations based on gender and roles were studied.Methods:It is an analytical comparative cross-sectional study in which seven PBL groups were selected per year by non-probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
7
0
5
Order By: Relevance
“…We found five studies in this scoping review that focused on these outcomes and all of them described that a curriculum centered on PBL seems to instill more confidence in social and communication skills among students. Students perceived PBL positively for teamwork, communication skills and interpersonal relations [ 44 , 45 , 67 , 75 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found five studies in this scoping review that focused on these outcomes and all of them described that a curriculum centered on PBL seems to instill more confidence in social and communication skills among students. Students perceived PBL positively for teamwork, communication skills and interpersonal relations [ 44 , 45 , 67 , 75 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of the PBL methodology has also been explored in other outcomes such as the ability to solve problems and to self-directed learning. All studies have shown that PBL is more effective than lecture-based learning in problem-solving and self-learning skills [ 18 , 24 , 40 , 48 , 67 , 75 , 93 , 104 , 124 ]. One single study found a poor accuracy of the students’ self-assessment when compared to their own performance [ 125 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found ve studies in this scoping review that focussed on these outcomes and all of them described that a curriculum centred on PBL seems to instil more con dence in social and communication skills among students. Students perceived PBL positively for team work, communication skills and interpersonal relations (Seneviratne et al 2001;Suleman et al 2010;Hande et al 2015;Al-Shaikh et al 2015;Mughal & Shaikh 2018).…”
Section: Social and Communication Skillsmentioning
confidence: 99%
“…The effectiveness of the PBL methodology has also been explored in other outcomes such as the ability to solve problems and to self-directed learning. All studies have shown that PBL is more effective than lecture-based learning in problem-solving and self-learning skills (Casassus et al 1999;Seneviratne et al 2001;Whit eld et al 2002;Ding et al 2014;Balendran & John 2017;Mughal & Shaikh 2018;Yadav et al 2018;Villamor 2001;Demiroren et al 2016).…”
Section: Other Outcomes and Descriptive Experiencesmentioning
confidence: 99%
“…-поведінкового -який виявляється через самопрезентацію та саморегуляцію, а результативно -через включеність у професійне співтовариство та сформованість професійної інтернальності (Денисова, 2008;Орбан-Лембрик, 2009;Mughal, 2018).…”
unclassified